Prevalence and prognostic value of non-thyroidal illness syndrome among critically ill children - Sohair Sayed Abu El-Ella; Muhammad Said El-Mekkawy; Mohamed Abdelrahman El-Dihemey (Elsevier, 2019)
Introduction: Alterations in thyroid hormones during critical illness, known as non-thyroidal illness syndrome (NTIS), were suggested to have a prognostic value. However, paediatric data is limited. The aim of this study was to assess prevalence and prognostic value of NTIS among critically ill children. Materials and methods: A prospective observational study conducted on 70 critically ill children admitted into paediatric intensive care unit (PICU). Free triiodothyronine (FT3), free thyroxine (FT4), and thyroid stimulating hormone (TSH) were measured within 24 h of PICU admission. Primary outcome was 30-day mortality. Results: NTIS occurred in 62.9% of patients but it took several forms. The commonest pattern was low FT3 with normal FT4 and TSH (25.7% of patients). Combined decrease in FT3, FT4, and TSH levels occurred in 7.1% of patients. An unusual finding of elevated TSH was noted in three patients, which might be related to disease severity. Low FT4 was significantly more prevalent among non-survivors compared with survivors (50% versus 19.2%, P = .028). NTIS independently predicted mortality (OR = 3.91; 95% CI = 1.006-15.19; P = .0491). Concomitant decrease in FT3, FT4, and TSH was the best independent predictor of mortality (OR = 16.9; 95% CI = 1.40-203.04; P = .026). TSH was negatively correlated with length of PICU stay (rs = -0.35, P = .011). FT3 level was significantly lower among patients who received dopamine infusion compared with those who did not receive it (2.1 ± 0.66 versus 2.76 ± 0.91 pg/mL, P = .011). Conclusion: NTIS is common among critically ill children and appears to be associated with mortality and illness severity. Resumen: Introducción: Se ha sugerido que las alteraciones en las hormonas tiroideas ocurridas en pacientes con enfermedad crítica, fenómeno conocido como síndrome del enfermo eutiroideo (SEE), pueden tener valor pronóstico. No obstante, los datos en población pediátrica son escasos. El objetivo del estudio fue evaluar la prevalencia y el valor pronóstico del SEE en niños críticos. Materiales y métodos: Estudio prospectivo observacional en 70 niños críticos ingresados en la unidad de cuidados intensivos pediátricos (UCIP). Se determinaron los niveles de triyodotironina libre (T3L), tiroxina libre (T4L) y tirotropina (TSH) en las primeras 24 horas de ingreso. La variable de resultado principal fue la mortalidad a los 30 días. Resultados: Se observó SEE en el 62,9% de los pacientes, aunque adoptó formas diversas. El patrón más frecuente fue un nivel bajo de T3L con niveles normales de T4L y TSH (25,7% de los pacientes). La combinación de valores bajos de T3L, T4L, y TSH ocurrió en el 7,1% de los pacientes. Hubo un hallazgo inusual de TSH elevada en 3 pacientes que podría estar asociado a la gravedad de la enfermedad. Los valores bajos de T4L se observaron con una frecuencia significativamente mayor en pacientes fallecidos en comparación con supervivientes (50% versus 19,2%, p = 0,028). El SEE predijo la mortalidad de manera independiente (OR = 3,91; IC 95% = 10,06-15,19; p = 0,0491). La combinación de niveles bajos de T3L, T4L, y TSH fue el mejor factor pronóstico independiente de mortalidad (OR = 16,9; IC 95% = 1,40-203,04; p = 0,026). Se observó una correlación negativa entre la TSH y la duración de la estancia en la UCIP (rs = -0,35; p = 0,011). El valor de T3L fue significativamente menor en pacientes tratados con perfusión de dopamina, comparados con pacientes que no la recibieron (2,1 ± 0,66 versus 2,76 ± 0,91 pg/ml, p = 0,011). Conclusión: El SEE es común en niños críticos y parece estar asociado a la mortalidad y la gravedad de la enfermedad.